(untitled) (Philological Studies, 2019)
This article is a comparative approach to so-called "Attributability" in songs "Seven approaches to motive Trembling aspen" of Gane Todorovski and "Violet" of Antun Gustav Matosh. Three corpuses of meaning entities that allow insight into the metaphoricity of the Macedonian poet song, and the symbolism of the Croatian poet song are analyzed. This is done so that the metaphors and symbols are gramatically “decomposed" in order to follow the process of transformation of “meaning” to “sense”. It all comes down to the only meoning - human life.